Moxifloxacin Metal Complexes: Synthesis, Characterisation, Antimicrobial and Antidiabetic Activities with Docking Studies - Sajjad Ali; Huaiji Zheng; Asma Zaidi; Farhan Ahmed Khan; Syed Majid Bukhari; Muhammad Riaz; Muhammad Mumtaz Khan; Shehla Sammi; Inham u-llah; Ammad Amin; Muhammad Jahangir (Bioinorganic Chemistry and Applications)
Six new metal complexes of Fe(III), Cu(II), and Hg(II) were synthesised, i.e., three (2, 4, and 5) with moxifloxacin (mono-ligand) and the other three (1, 3 and 6) with moxifloxacin and hydrazine (biligand). These were characterised through UV-Vis, FT-IR, elemental analysis (CHN), atomic absorption spectroscopy, TGA, scanning electron microscopy (SEM), and powder XRD studies. Further, all of these compounds were screened for their antimicrobial, cytotoxic, and antidiabetic potential. The study revealed that the synthesised metal complexes possess an excellent ability to become antifungal agents compared to moxifloxacin. Additionally, the cytotoxicity of compounds 1, 3, and 4 was in the acceptable range with much better antidiabetic potential as compared to the ligand moxifloxacin. Interestingly, the α-amylase inhibition activity of complexes 1 and 3 was found very close to the standard drug acarbose. Furthermore, the computational studies also authenticate the results of the antidiabetic potential of complexes 1, 3, and 4 by presenting the necessary interactions of these compounds with their respective binding sites. The overall results indicate that the antifungal and antidiabetic ability of moxifloxacin is enhanced significantly by complexation with the given metals and the secondary ligand, thereby making it a suitable lead compound for yet another avenue of an antifungal and antidiabetic agent in the field of drug discovery and development.